Financial Evaluation Study on Maintenance Project of Irrigation Facilities (Case Study on Sumber Kedung Kandang Irrigation Sector, Kademangan Village, Gondang Legi, Malang) - Suharto, Bambang; Wirosoedarmo, Ruslan; Kurniawan, Achmad (Jurnal Teknologi Pertanian, 2001)
Irrigation development as a completed process, need monitoring and evaluation mechanism. It is use to help and to learn development dynamics. This research aimed for financial evaluation of irrigation project and to know economic efficiency of maintenance and operation irrigation facilities. Financial evaluation study did in Sumber Kedung Kandang irrigation sector, Kademangan village on November 2000. Completely randomized sampling did on 40 : 60 proportion, 95% probability limit and standard error 15%. From this condition, respondent must be interviewed is 41 person. This result showed production increase after irrigation facilities established, i.e. 5 â€“ 7%. Financial evaluation showed it is feasible project, from the IRR value, i.e. 12% and the NPV value, i.e. Rp. 2.041.687.650,31. The BEP time of irrigation structure is 5 years, 6 months, and 11 days. The depreciation of it is Rp. 420.000 on 25 years period and residue value is Rp. 4.500.000. the operation and maintenance activities economically good enough, with IPL value after project increase for corn, sugar cane and rice from 0,10 to 0,11; 0,0127 to 0,0161 and 0,059 to 0,069 respectively. Â  Keywords: irrigation facilities, financial evaluation, irrigation development